If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-88=-8(-7+3n)+6n
We move all terms to the left:
-88-(-8(-7+3n)+6n)=0
We add all the numbers together, and all the variables
-(-8(3n-7)+6n)-88=0
We calculate terms in parentheses: -(-8(3n-7)+6n), so:We get rid of parentheses
-8(3n-7)+6n
We add all the numbers together, and all the variables
6n-8(3n-7)
We multiply parentheses
6n-24n+56
We add all the numbers together, and all the variables
-18n+56
Back to the equation:
-(-18n+56)
18n-56-88=0
We add all the numbers together, and all the variables
18n-144=0
We move all terms containing n to the left, all other terms to the right
18n=144
n=144/18
n=8
| --6(x+3)=3(x-15) | | -10w=-10-10w | | -2p+5p=3p | | 4−2(x−5)=x−19 | | -8c-10=-10-8c | | 6+d=3d | | -5r+9r=17+6r-1 | | 3(x+5)-2x=3(x-4)-2x | | -10(z−85)=-100 | | 1-6m=-6m+1 | | 5x-3+2x=-3+7x | | -r+4=4-r | | 24+21.5m=41+17.25 | | 0=3w^2+3w-2 | | 93=4(3m-2)+5 | | -13d-10d+1=-20d-20 | | 4f-10=-9+4f | | f9− -47=49 | | 82=17+5g | | 7(w+4)=98 | | -8(x+5)=4(x+170 | | -5+6y=4+9y | | d/4+24=28 | | 7d-3=-3+7d | | 3(x=5)-2x=3(x-4)-2x | | 95=5(z+8) | | 4+4s=6+4s | | -6(x-6)=2(x=14) | | 40=2(j+12) | | -4(1-2n)+5n=95 | | 45=9f+18 | | 1-4p=4-4p |